Presupuesto participativo y rendición de cuentas en la provincia de Requena 2024 - Perez Torres, Silvia Raquel (2025)
The final report is outlined as my ultimate goal. To explore how participatory budgeting and transparency intertwine in Requena in 2024. The population analyzed included 382 individuals, who were given a questionnaire to collect data. This was explored using descriptive-correlational analysis and a non experimental strategy. The study included 382 residents, who were given a questionnaire to collect information. The findings reveal that collaborative budgeting remains at a modest 25%. In contrast, transparency is perceived as moderate (26%). Furthermore, a moderate to robust positive connection was discovered, with a coefficient of 0.755, between participatory budgeting and transparency, with zero significance. Next, a readiness coefficient (ρ=0.657, p value=0.000) is revealed that transcends with moderation; Furthermore, concertation exhibits a coefficient (ρ=0.655, p-value=0.000) that transcends strongly; and, finally, coordination exhibits a coefficient (ρ=0.589, p value=0.000) that transcends strongly.